"From 'Guru-mukha' to Contemporaneity": metamorphosing divergent trajectories of Mohiniyattam pedagogy and performativity. Issue 2 (5th April 2021) - Rajan, Aswathy
Abstract : This article foregrounds the various modalities in which a South Indian feminine dance form, Mohiniyattam is taught and performed, and underscores its metamorphosis from an erotic practice to a significant art form. It traces the paradigm shift that Mohiniyattam underwent from its purist-traditionalist form to the present phase and the pedagogic changes that such a shift necessitated.